2016
DOI: 10.1007/978-981-287-988-2_35
|View full text |Cite
|
Sign up to set email alerts
|

Performance Evaluation of Welded Knitted E-Fabrics for Electrical Resistance Heating

Abstract: This paper presents a study conducted on electrical resistance heating of knitted e-fabric structures including silver plated conductive yarns. The study further investigates the application of ultrasonic welding technology on these knitted e-fabrics in order to see their effect on heating performance. Thermal analysis was carried out under different voltage values to observe temperature variations over the knitted e-fabrics. It was found that the linear resistance of conductive yarns and its interaction with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…20 For the manufacturing of e-textiles, continuous ultrasonic plastic welding was firstly investigated to be used for bonding conductive stripes as transmission lines onto textile substrates. [21][22][23] Another study reported that currentcarrying textile-based conductor strips for contacting heatable nonwovens can also be processed using the continuous welding process. 24 The latest publications describe the investigations into ultrasonic spot welding as a technology for connecting textile-integrated conductors.…”
mentioning
confidence: 99%
“…20 For the manufacturing of e-textiles, continuous ultrasonic plastic welding was firstly investigated to be used for bonding conductive stripes as transmission lines onto textile substrates. [21][22][23] Another study reported that currentcarrying textile-based conductor strips for contacting heatable nonwovens can also be processed using the continuous welding process. 24 The latest publications describe the investigations into ultrasonic spot welding as a technology for connecting textile-integrated conductors.…”
mentioning
confidence: 99%
“…Three trajectory patterns were prepared. Due to limitations in performance of spacer fabric knitting machines, and after further extended practical and theoretical knowledge, the final designs were characterised with the following features [31,32]:placement of a heating element was unidirectional,the straight trajectory of the heating element line was avoided not to limit the stretchability of the base material,the trajectory of a heating element within one design was kept in even distance in order to provide the most uniform heating,the smallest distance between heating yarns was 1 cm to avoid hotspots. Step 2. Calculating the resistance needed to obtain the estimated power of the whole mat…”
Section: Experiments Methodsmentioning
confidence: 99%
“…Preparation of the trajectories of heating cables Three trajectory patterns were prepared. Due to limitations in performance of spacer fabric knitting machines, and after further extended practical and theoretical knowledge, the final designs were characterised with the following features [31,32]:…”
Section: Experiments Methodsmentioning
confidence: 99%
“…Conductive textiles are traditional textiles that incorporate conductive fibers or other types of materials employing different technologies, and they are widely used in many fields [1,2], such as sensors [3,4,5,6,7,8], heaters [9,10,11], capacitors [12,13], and electromagnetic shielding fabrics [14]. In addition, knitting technology has become more and more popular in forming conductive textiles because the method produces a flexible structure and shape for the final product.…”
Section: Introductionmentioning
confidence: 99%